Synchrophasing Vibration Control of Machines Supported by Discrete Isolators - Huang, Di; Yang, Tiejun; Liu, Zhigang; Brennan, Michael J. [UNESP]; Li, Xinhui (Springer Nature, 2019)
This paper describes an analytical investigation into synchrophasing, a vibration control strategy on a machinery installation in which two rotational machines are attached to a beam-like raft by discrete resilient isolators. Forces and moments introduced by sources are considered, which effectively represent a practical engineering system. Adjusting the relative phase angle between the machines has been theoretically demonstrated to greatly reduce the cost function, which is defined as the sum of velocity squares of attaching points on the raft at each frequency of interest. The effect of the position of the machine is also investigated. Results show that altering the position of the secondary source may cause a slight change to the mode shape of the composite system and therefore change the optimum phase between the two machines. Although the analysis is based on a one-dimensional Euler–Bernoulli beam and each machine is considered as a rigid-body, a key principle can be derived from the results. However, the factors that can influence the synchrophasing control performance would become coupled and highly complicated. This condition has to be considered in practice.
Keywords: Different forms of excitations; Discrete supported machines; Raft; Synchrophasing control; Vibration isolation